Analisis Penggunaan Fisika Kuantum Dalam Pengembangan Komputasi Kuantum - Daeli, Mikhael Oktoberyan Sawato Ziduhu; Telaumbanua, Mercy; Lase, Lenalestari (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze literature related to the application of quantum physics principles in the development of quantum computing technology. Quantum computing is a rapidly evolving field that holds significant potential for solving complex problems that classical computers cannot efficiently address. By reviewing recent studies, this research discusses fundamental concepts such as superposition, entanglement, and quantum decoherence, as well as their applications in quantum algorithms, including Shor’s and Grover’s algorithms. Furthermore, the article explores the challenges and future prospects of developing stable and practical quantum computers. The findings indicate that although significant advancements have been made in technology and theory, major challenges such as decoherence control and qubit scaling remain key areas for future research.